2017
DOI: 10.5194/amt-10-333-2017
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for the effects of surface BRDF on satellite cloud and trace-gas retrievals: a new approach based on geometry-dependent Lambertian equivalent reflectivity applied to OMI algorithms

Abstract: Abstract. Most satellite nadir ultraviolet and visible cloud, aerosol, and trace-gas algorithms make use of climatological surface reflectivity databases. For example, cloud and NO 2 retrievals for the Ozone Monitoring Instrument (OMI) use monthly gridded surface reflectivity climatologies that do not depend upon the observation geometry. In reality, reflection of incoming direct and diffuse solar light from land or ocean surfaces is sensitive to the sun-sensor geometry. This dependence is described by the bid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
101
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(105 citation statements)
references
References 44 publications
4
101
0
Order By: Relevance
“…With the currently adopted AMF estimates we anticipate an overall reduction in the OMI-derived top-down anthropogenic NO x emissions and surface concentrations. However, applying a new geometry-dependent Lambertian equivalent reflectivity in AMF calculation would result in increasing tropospheric VCDs (Vasilkov et al, 2017) and derived top-down NO x emissions and surface concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the currently adopted AMF estimates we anticipate an overall reduction in the OMI-derived top-down anthropogenic NO x emissions and surface concentrations. However, applying a new geometry-dependent Lambertian equivalent reflectivity in AMF calculation would result in increasing tropospheric VCDs (Vasilkov et al, 2017) and derived top-down NO x emissions and surface concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In the free troposphere, W i,trop increases with altitude and strongly depends on the cloud radiance fraction and optical centroid pressure Vasilkov et al, 2009). In the boundary layer and under cloud-free conditions, W depends most strongly on altitude and surface pressure and reflectance (Vasilkov et al, 2017). The AMF for a stratospheric or tropospheric column is computed as the vertical integral of the NO 2 profile shape weighted average of W (Eq.…”
Section: Amf Calculationmentioning
confidence: 99%
“…Vasilkov et al (2017) also found increased differences in the tropospheric AMFs due to surface BRDF effects on cloud parametes, but as reported by Lin et al (2014), there can also be compensating effects.…”
mentioning
confidence: 62%
“…The indirect effect of biased cloud parameters on NO 2 retrievals combined with effects on clear-sky AMFs received less attention. Vasilkov et al (2017) and Lin et al (2015) addressed the indirect effects and showed that the effects on cloud parameters could enhance or compensate the direct effect on clear-sky AMFs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation